The Correlation Between Intensity and Body Posture in Gadget Use and Eye Strain (Asthenopia) on Medical Record Students at Poltekkes Kemenkes Tasikmalaya - Gita Sesaria, Tifanny; Komarudin, Komarudin; Ari Andini, Saskiyanti; Irawan, Chandra; Ramadhan, Sahrir (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2025)
Devices or gadgets are an example of technology that is developing and helping many jobs in various fields, including in hospitals. One profession that uses a lot of devices (laptops, computers and cellphones) is medical records.  Currently, recording patient medical records in several hospitals has switched to using Electronic Medical Records (RME) so that it requires being in front of a laptop for a long time. The development of computerized systems does not always have a positive impact on users, there are several health problems that often occur, one of which is eye fatigue (asthenopia). The aim of this research is to determine the correlation between intensity and body posture on eye fatigue in medical records students at the Tasikmalaya Health Polytechnic. The research design in this study uses a cross-sectional. The respondents were 57 students of Polytechnic Tasikmalaya and experince using personal computer and gadgets. The analysis used is univariate to obtain an overview and describe each variable by presenting the data using cross tabulation. The result showed a significant effect on intensity of using gadget on eye fatigue (astenophia) with a p-value : 0.035. It is important to maintain a good posture and manage the intensity of using gadget in order to maintain eye health.